2021
DOI: 10.3390/vaccines9111294
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of MERTK and FLT3 Induce Cell Cycle Arrest in Human CD8+ T Cells

Abstract: There is an increasing interest in the development of Receptor Tyrosine Kinases inhibitors (RTKIs) for cancer treatment, as dysregulation of RTK expression can govern oncogenesis. Among the newer generations of RTKIs, many target Mer Tyrosine Kinase (MERTK) and Fms related RTK 3 (FLT3). Next to being overexpressed in many cancers, MERTK and FLT3 have important roles in immune cell development and function. In this study, we address how the new generation and potent RTKIs of MERTK/FLT3 affect human primary CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Through the DEGs related to low CTL activity from both studied cohorts, we identified potential treatment compounds with lower negative connectivity scores (τ > −90) that could potentially reverse CTL resistance. The perturbational class identified in our study, namely PI3K inhibitors [ 49 ], mTOR inhibitors [ 50 ], IGF-1 inhibitors [ 51 ], JAK inhibitors [ 52 ], DNA dependent protein kinase inhibitors [ 53 ], HDAC inhibitors [ 54 ], and FLT3 inhibitors [ 55 ], were also reported to mediate immune modulation in various cancers. Further high-throughput chemical libraries screening identified 133 small inhibitors that could target both PDAC parental and CTL-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through the DEGs related to low CTL activity from both studied cohorts, we identified potential treatment compounds with lower negative connectivity scores (τ > −90) that could potentially reverse CTL resistance. The perturbational class identified in our study, namely PI3K inhibitors [ 49 ], mTOR inhibitors [ 50 ], IGF-1 inhibitors [ 51 ], JAK inhibitors [ 52 ], DNA dependent protein kinase inhibitors [ 53 ], HDAC inhibitors [ 54 ], and FLT3 inhibitors [ 55 ], were also reported to mediate immune modulation in various cancers. Further high-throughput chemical libraries screening identified 133 small inhibitors that could target both PDAC parental and CTL-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…FLT3 propagates signals in the cell to maintain cellular functional activity, and its ligand is also important for inducing cancer relapse and antitumor immune reactions [ 35 ]. Powell et al [ 36 ] reported that FLT3 could contribute on the penetration of CD8+ T cells and stimulatory dendritic cells in the microenvironment, further affecting the growth of cancers. C1QC, a crucial part of the classical complement pathway, yet there are few studies on C1QC in CM.…”
Section: Discussionmentioning
confidence: 99%